INTERPRETATIONS OF TERRORISM: THEORETICAL AND PRACTICAL APPROACHES - AKAEV, Vakhit; KELIGOV, Murat; NANAEVA, Boryat (CENTRAL ASIA AND THE CAUCASUS, 2018)
The variety of specific forms of terrorism and, therefore, its different interpretations are rooted in social, economic, political, geopolitical, and religious factors. Theoretical and practical approaches to terrorism help identify its most important characteristics, global and regional specifics, and the ways and means to be used to combat it. A clearer idea of regional specifics of terrorist manifestations suggests specific forms of prevention and counteraction. Sociological polls among North Caucasian students, in the Chechen Republic in particular, serve precisely this purpose. Prevention depends, first and foremost, on a better understanding of the causes of asocial behavior of those young men who fell into the trap of criminal groups; better understanding is achieved through finding out what the students of the Chechen Republic think about extremism and terrorism.